Pengembangan Media Pembelajaran Electronic Book (E-Book) Pada Mata Pelajaran Praktikum Akuntansi Perusahaan Dagang - Deby Rahmita Maulida; Joni Susilowibowo (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
The rapid development of learning resources following the times to support and support learning in schools, sometimes there are still many school there are not able to provide adequate and complete learning resources. Emergence of an innovative solution to overcome to problem to the SMK. Therefore, the developer tries to develop learning media with e-book teaching materials. This research was conducted with the aim of e-book product. With the selection of recording material and summarizinf the accounting practicum of trading companies. This study uses a 4D research model, but only up to the development stage. The result of the expert validation assessmenton the e-book obtained the “Very Eligible” criteria.